Considerations Regarding the Parents’ Opinions About the Physical Education Lesson in the Secondary Schools of Reșița - ROHOZNEANU, Dan-Mihai (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Parents’ attitudes towards physical education lessons can have a significant impact on children and their participation in physical education lessons. If parents show disinterest or have a negative attitude towards the lesson and the physical education teacher, children may receive a signal that this activity is not important, causing them to be reluctant to engage in physical education lessons, to avoid these activities, to engage in sedentary activities, which can contribute to increasing the risk of obesity and other conditions. The purpose of our research is to find out the opinions of the parents of secondary school students regarding the lesson of physical education and sports. We used the questionnaire-based survey method and the graphic method. Questionnaires were applied to the parents of students from educational institutions in the municipality of Reșita. The answers showed that parents are aware of the importance of physical education and sports classes alongside other school subjects, sports making children happier, more motivated in terms of choosing a sport to practice in their free time. Article history: Received 2025 April 10; Revised 2025 May 29; Accepted 2025 June 03; Available online 2025 July 30; Available print 2025 August 30